2022
DOI: 10.1111/cts.13375
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of metformin‐mediated BSEP repression on pravastatin and bile acid pharmacokinetics in humans: A randomized controlled trial

Abstract: Metformin has been shown to repress transcription of the bile salt export pump (BSEP) in human primary hepatocytes. The primary objective of this study was to assess the effect of oral metformin on the human pharmacokinetics (PKs) of two BSEP probe substrates: pravastatin and chenodeoxycholic acid (CDCA; also known as chenodiol). Endogenous bile acid levels were assessed as a secondary measure of metformin impact. An open‐label, randomized, single‐dose, placebo‐controlled, fasted, crossover PK study was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Bile acid measurements were performed using liquid chromatography-tandem mass spectrometry (LC-MS/MS) as previously described ( 27 , 28 , 29 ). Briefly, 100 μl of plasma were loaded directly onto the ISOLUTE PLD+ column per manufacturer’s instructions, and 5 μl of internal standard (1 μg/ml deuterated bile acids stock) was added to each tube.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bile acid measurements were performed using liquid chromatography-tandem mass spectrometry (LC-MS/MS) as previously described ( 27 , 28 , 29 ). Briefly, 100 μl of plasma were loaded directly onto the ISOLUTE PLD+ column per manufacturer’s instructions, and 5 μl of internal standard (1 μg/ml deuterated bile acids stock) was added to each tube.…”
Section: Methodsmentioning
confidence: 99%
“…Homogenate was centrifuged at 4000 rpm for 5 min, and 600 μl of supernatant was combined with 30 μl of internal standard and 3 ml of 5% ammonium hydroxide to precipitate proteins. Samples were then allowed to shake at room temperature for 2 h and the organic layer was then passed through the PLD+ column and reconstituted as listed above ( 27 , 28 , 29 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, it's worth noting that these studies do not measure changes of BA concentrations. In addition, many studies have reported that metformin can inhibit the expression of the bile acid transporter BESP by activating cAMP-PKA and cAMP-AMPK pathways, although it does not appear to affect the expression of CYP7A1 [38][39][40]. This implies that metformin may influence not only bile acid synthesis, but also bile acid secretion and reuptake.…”
Section: Bile Acids and Diabetes Drugs (Metformin And Acarbose)mentioning
confidence: 99%